Pengaruh Penggunaan Sistem Pos (Point Of Sale) Dan E-Commerce Terhadap Pendapatan Usaha Cafe Di Kabupaten Mamuju - Sandra Winata; Nabila; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
The development of information technology encourages business actors to adopt digital systems to improve business performance. The use of Point of Sale (POS) systems and e-commerce is one form of Management Information System implementation widely applied in café businesses. This study aims to analyze the effect of POS systems and e-commerce usage on the income of café businesses in Mamuju Regency. The research method used is a quantitative approach with a descriptive research design. Data were collected through questionnaires distributed to café owners and managers who have implemented POS systems and e-commerce. The research variables include the use of POS systems, the use of e-commerce, and business income. The results indicate that the use of POS systems and e-commerce has a positive effect on café business income. POS systems improve transaction recording efficiency and sales management, while e-commerce expands market reach and increases the number of customers. Therefore, the utilization of technology-based information systems can support the increase of café business income in Mamuju Regency.